2006
DOI: 10.1002/jms.1044
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous separation and identification of oligomeric procyanidins and anthocyanin‐derived pigments in raw red wine by HPLC‐UV‐ESI‐MSn

Abstract: Samples of raw red wine (Primitivo di Manduria, Apulia, Southern Italy) were analysed without any pre-treatment (except 1:2 dilution with water) using HPLC with detection based on UV absorbance and Electrospray Ionisation Sequential Mass Spectrometry (ESI-MSn, with n = 1-3) in a series configuration. In particular, absorbance at 520 nm was monitored for UV detection in order to identify pigments responsible for wine colour. On the other hand, two subsequent stages of MS detection based on positive ions were ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
67
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 42 publications
9
67
1
Order By: Relevance
“…We observed the loss of a sugar moiety, the loss of monomer (D290 amu), A-type dimer (D576 amu) or B-type dimer (D578 amu) and the simultaneous loss of sugar and monomer or dimer. The same fragmentation pattern was observed by Pati et al (2006) for ethyl-bridged anthocyanin-(epi)catechin pigments in red wine. Reed et al (2005) reported in a similar study on a cranberry extract the detection of these 10 ions along with two additional ions at m/z 1023 (cyanidin-pentoside-ethyl-B-type dimer) and at m/z 1053 (cyanidin-hexoside-ethyl-B-type dimer).…”
Section: Characterisation Of the Osa7 Cranberry Extractsupporting
confidence: 78%
“…We observed the loss of a sugar moiety, the loss of monomer (D290 amu), A-type dimer (D576 amu) or B-type dimer (D578 amu) and the simultaneous loss of sugar and monomer or dimer. The same fragmentation pattern was observed by Pati et al (2006) for ethyl-bridged anthocyanin-(epi)catechin pigments in red wine. Reed et al (2005) reported in a similar study on a cranberry extract the detection of these 10 ions along with two additional ions at m/z 1023 (cyanidin-pentoside-ethyl-B-type dimer) and at m/z 1053 (cyanidin-hexoside-ethyl-B-type dimer).…”
Section: Characterisation Of the Osa7 Cranberry Extractsupporting
confidence: 78%
“…This molecular ion corresponds to the compound obtained in the cycloaddition of pyruvic acid to peonidin-3-O-glucoside known as vitisin A of peonidin-3-O-glucoside (Fulcrand et al, 1998). It has been previously reported in red wines (Alcalde-Eon et al, 2007;Atanasova et al, 2002;Pati et al, 2006). On the other hand, the reaction of malvidin-3-O-glucoside and acetaldehyde in wine model solution showed, by ESI/MS analysis after 48 h, the formation of a malvidin-3-O-glucoside dimer mediated by acetaldehyde, with a molecular ion at m/z 1012.…”
Section: Anthocyanins Characterisationmentioning
confidence: 72%
“…Also acetyl, coumaryl and caffeyl-glucosides were detected. Pati et al (2006) reported the formation in young red wine of condensation products of malvidin-3-O-glucoside with catechin and epicatechin mediated by ethyl or vinyl bridges. The resolution of the chromatograms over 50 min is low, which indicates that compounds with molecular weights between m/z 900 and 1500 are co-eluting (Fig.…”
Section: Anthocyanins Characterisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantification by ESI/MS of anthocyanins present in grape extract can be done by constructing a calibration curve using two commercially available standard compounds, the Mv-3-O-glucoside (M+ species at m/z 493) for monoglucosides and the Mv-3,5-O-diglucoside (M+ species at m/z 655) for diglucosides [44].…”
Section: Grapes and Wines -Advances In Production Processing Analysmentioning
confidence: 99%